Novel applications of genetic evaluation in livestock: gas fluxes and metabolic heat production in grazing beef cattle, and cashmere fiber in goats of two origins - Dressler, Elizabeth Anne (My University, 2025)
Two distinct genetic evaluations were performed, each offering novel contributions within their respective species. The first was a genetic evaluation of gas fluxes and metabolic heat production in grazing Angus beef cattle, which are emerging, but understudied traits. The second was a genetic evaluation of cashmere fiber characteristics in goats from two origins: the United States and New Zealand. While cashmere fiber traits have been studied more extensively, a genetic evaluation for U.S. cashmere goats had never been published before. Cashmere producers, particularly in the United States where no genetic selection tools currently exist, would greatly benefit from the development of a national cashmere fiber genetic evaluation system. In this study, three genetic evaluations for cashmere fiber traits were performed depending on the goat’s origin: U.S., New Zealand, and combined from both origins. International collaboration and data sharing were leveraged to increase sample size and strengthen the accuracy of the evaluations, given that there was gene flow between the two populations. Producers voluntarily submitted fiber samples to either the Texas A&M Bill Sims Wool and Mohair Research Laboratory (San Angelo, Texas) or SGS Wool Testing Services (Kilbirnie, New Zealand). A total of 3,336 fiber records from 2,572 goats were available between the U.S. and New Zealand. Fiber traits studied in all three analyses included mean fiber diameter (MFD), standard deviation of diameter (SDD), coefficient of variation of diameter (CVD), curvature (CURV), standard deviation of curvature (SDCURV), spinning fineness (SpinF), and percentage of fibers with diameter ≤ 19 µm (Perc19). Additional fiber traits analyzed in the U.S.-only analysis were staple length, greasy fleece weight, and coarse edge micron. Additional fiber traits analyzed in the N.Z.-only analysis were down staple length, yield, fleece weight, down weight, coarse edge, and percentage of medullated fibers. All animals were genotyped using the Goat GGP 70K BeadChip (Neogen Corp.) and pedigree records were provided by participating producers. Variance components for each trait were estimated using single step genomic BLUP (ssGBLUP) with the BLUPF90 suite of programs. Fixed effects tested for model inclusion were age at fiber collection, sex, and contemporary group. In general, heritability estimates for shared traits were similar and moderate to high across all three analyses. In the combined analysis, the heritability of MFD, SDD, CVD, CURV, SDCURV, SpinF, and Perc19 was 0.46 ± 0.04, 0.26 ± 0.04, 0.26 ± 0.04, 0.33 ± 0.04, 0.24 ± 0.04, 0.40 ± 0.04, and 0.29 ± 0.04. Repeatability of cashmere fiber traits were moderate to high. Mean fiber diameter had unfavorable genetic correlations with CVD and SCURV. Genome-wide association studies identified several significant single nucleotide polymorphisms (SNPs) for cashmere traits. Many candidate genes located within ± 50 kb of these SNPs have been previously associated with fiber related biological processes or skin and hair biology in other species, including humans and mice. These findings demonstrate that cashmere fiber traits are heritable, and that genetic improvement through selection is feasible. Together, these findings provide a foundational resource for future development of a selection tool for cashmere goat breeding. Ruminant animals produce methane (CH₄) as a by-product of enteric fermentation, a digestive process unique to ruminants. In beef cattle, CH₄ production represents both an energetic inefficiency and environmental concern. Methane mitigation efforts in grazing beef cows have the potential to have greater impact within the beef industry than mitigation within any other sector. Methane, carbon dioxide (CO₂), and oxygen (O₂) fluxes were collected from 330 grazing Angus beef females using a GreenFeed system. These gas fluxes were used to calculate metabolic heat production (MHP). All available fluxes were either averaged for the single record analysis or each visit to the GreenFeed system was treated as an individual record in the repeat-record analysis. A pedigree for phenotyped animals, as well as genotypes for animals with gas flux data and their relatives were provided by the American Angus Association (Saint Joseph, Missouri). Variance components were estimated using the BLUPF90 software suite and the single step genomic BLUP methodology in both the single record and repeated records analyses. Fixed effects tested for model inclusion included contemporary group (GreenFeed trial group), age at GreenFeed trial start, body condition score, and mature weight estimated progeny difference (EPD). In the single record analysis, the heritabilites of average CH₄, average CO₂, average O₂, and average MHP were 0.23 ± 0.16, 0.32 ± 0.15, 0.20 ± 0.15, and 0.24 ± 0.15, respectively. In the repeated records analysis, the heritabilities of CH₄, CO₂, O₂, and MHP were 0.09 ± 0.03, 0.14 ± 0.04, 0.12 ± 0.04, and 0.13 ± 0.04, respectively. The repeatability of gas flux traits and MHP was low, ranging from 0.14 ± 0.01 to 0.21 ± 0.02. Estimated progeny differences (EPD) were generated for gas flux traits and MHP. Correlations between these gas flux EPDs and EPDs for other production traits and economic index values were calculated. Notably, gas flux and MHP EPDs had significant correlations with EPDs related to weight and feed intake, as well as economic index values. Significant single nucleotide polymorphisms for average gas flux traits were near QTLs previously associated with body weight, dry matter intake, residual feed intake, and average daily gain. This study provides preliminary genetic parameter estimates for gas fluxes and metabolic heat production in grazing beef cattle.
Keywords: Genetic evaluation; Beef cattle; Cashmere fiber; Greenhouse gas; Heritability